Effects of Different Treatment of Fecal Microbiota Transplantation Techniques on Treatment of Ulcerative Colitis in Rats - Zhu, Fangyuan; Ke, Yifan; Luo, Yiting; Wu, Jiaqian; Wu, Pei; Ma, Fangxiao; Liu, Yingchao (Frontiers in Microbiology, 2021)
Background: Ulcerative colitis (UC) is a chronic non-specific inflammatory bowel disease with abdominal pain, mucus, pus, and blood in the stool as the main clinical manifestations. The pathogenesis of UC is still not completely clear, and multiple factors such as genetic susceptibility, immune response, intestinal microecological changes, and environmental factors together lead to the onset of UC. In recent years, the role of intestinal microbiota disturbances on the pathogenesis of UC has received widespread attention. Therefore, faecal microbiota transplantation (FMT), which changes the intestinal microecological environment of UC patients by transplantation of normal faecal bacteria, has attracted increasing attention from researchers. However, there are no guidelines at home and abroad to recommend fresh FMT or frozen FMT in the treatment of UC, and there are few studies on this. Therefore, the purpose of this experiment was to explore the effects of fresh and frozen faecal microbiota transplantation methods on the treatment of experimental UC models in rats. Results: Compared with the model control group, all faecal microbiota transplantation groups achieved better efficacy, mainly manifested as weight gain by the rats, improvements in faecal characteristics and blood stools, reduced inflammatory factors, and normal bacterial microbiota. The efficacy of the frozen faecal microbiota transplantation group was better than that of the fresh faecal microbiota transplantation group in terms of behaviour and colon length. Conclusions: FMT is a feasible method for treating UC; the underlying mechanism may be associated with its supplementation of beneficial bacteria, such as short-chain fatty acid-producing bacteria. These can not only produce short-chain fatty acids to regulate intestinal function and protect the mucosal barrier, but also reduce harmful bacteria, thereby mitigating the damage to the intestinal barrier and the associated inflammatory response, resulting in UC remission. Compared with fresh FMT, the therapeutic effect of frozen FMT may be greater.